البحث النقدي والبلاغي في التراث بين فوضى المفاهيم و صرامة التقسيم - سفيان ., بلعجين (Université de M'sila, 2019)
حيكت المنظومة اﻻصطلاحية في البلاغة العربية بكثافة خيطية متداخلة و متشابكة لدرجة ان محاولة الوصول بتلك الخيوط إلى مسارها القويم أمر من الصعوبة بمكان. مما يعني غياب نسق اصطلاحي تنتظم و تتحدد فيه المصطلحات و المفاهيم. هذا من جهة، ومن جهة أخرى تعدد السياقات المعرفية التي تداخلت معها البلاغة حد التماهي على غرار النقد متلا جعل دلك من التعدد و اﻻضطراب و اﻻختلاف و التداخل مسرحا للغموض و التأزم ... ومن ثم لم ير البلاغيون...ﻻسيما المتأخرين منهم ...بأسا في وضع حد لدلك اﻻضطراب بتقسيمهم البلاغة أقسام تحت طائل التنظيم و الحد من الفوضى ...فجعل السكاكي البلاغة في ثلاثة أقسام ...البيان و المعاني و البديع ...وتبعه في دلك الخطيب القزويني ...بيد أن دلك التقسيم قد حوّل البلاغة من وصف فني إلى وصف علمي عقلاني محدد...و صارت البلاغة مجموعة قواعد...مثلها مثل النحو..هذا كله أدى إلى قتل البلاغة و تجريدها من روحها ...فزاد ذلك من تعقيد المشهد البلاغي في تراثنا العربي. The syntactic system in Arab rhetoric is woven with a dense, interlocking thread, so tangled that trying to reach those threads to its proper path is difficult. Which means the absence of a format in which terminology and concepts are defined. On the one hand, and on the other hand, the multiplicity of cognitive contexts in which rhetoric has interfered with the definition of criticism, such as criticism, which has led to a multiplicity, confusion, dissimilarity and overlap, a scene of uncertainty and crisis. And then did not see the plagions ... especially the late ones ... Basa to put an end to the turmoil by dividing them rhetoric divisions under the interests of regulation and reduce chaos ... Sakaki made rhetoric in three sections ... Statement and meanings and wonderful ... Followed by the Khateeb al-Qazwini ... However, the division has transformed rhetoric from technical description to specific rational scientific description ... and the rhetoric has become a set of rules ... like the grammar .. All this led to the killing of rhetoric and stripped of its soul. .. This led to the complexity of the rhetorical scene in our Arab heritage.
Keywords: البلاغة ، الاستعارة ، النقد العربي ، علم البديع، علم المعاني ، علم البيان